AB0197 Sonographic assessment of steroid injection therapy. (1st June 2001) - Filippucci, E; Farina, A; Salaffi, F; Cervini, C; Grassi, W
Abstract : Background: Ultrasonography (US) is an excellent technique to look around and inside joints and tendons in patients with chronic arthritis. 1 Power Doppler imaging combined with conventional grey-scale US could play a role in functional and quantitative assessment of synovitis. 2, 3 Objectives: The aim of this study was to assess sonographic changes induced by steroid injection therapy. Methods: Seven joints of 5 patients with active synovitis were studied. A visual analogue scale (VAS) (ranging from 0 to 10) and a tenderness score (ranging from 0 to 10) were assessed as measures of disease activity. Sonographic evaluation was performed with an AU-5 Harmonic, Esaote Biomedica (Genoa, Italy) equipped with a 13-MHz linear transducer. Power Doppler examination was performed just before the ultrasound guided injection with triamcinolone acetonide. Power Doppler settings were standardised with a pulse repetition frequency of 1000 Hz. Colour gain was initially set at a level just below the disappearance of colour noise deep to cortical bone. Joint cavity widening and power Doppler colour signal were scored from 0 to 4. Ultrasound examination was repeated in the second week after the steroid injection. Statistical evaluation was performed by the Wilcoxon signed-rank test. Results: All the affected joints showed both morphological (joint cavity widening) and functional (colour signal) features of active synovitis. A significant decrease of joint cavity widening (p = 0.045), VAS (p = 0.003), and tenderness score (p = 0.0024) was detected. Power Doppler score did not show a significant change (p = 0.091). However, a clearly evident decrease of colour signal was observed in 3 out of 5 patients. Conclusion: Our study confirms the clinical efficacy of steroid injection therapy. Grey-scale US seems to be able to carefully detect morphological changes induced by steroid injection therapy. Although this preliminary report shows that power Doppler score is not significantly changed after steroid injection, we believe that further studies on a larger group of patients are needed to better assess the role of power Doppler US in disease activity monitoring. References: Gibbon WW, Wakefield RJ. Ultrasound in inflammatory disease. Radiol Clin North Am. 1999;37:633–51 Hau M, Schultz H, Tony HP, Keberle M, Jahns R, Haerten R, Jenett M. Evaluation of pannus and vascularization of the metacarpophalangeal and proximal interphalangeal joints in rheumatoid arthritis by high-resolution ultrasound (multidimensional linear array). Arthritis Rheum. 1999;42:2303–8 Newman JS, Laing TJ, McCarthy CJ, Adler RS. Power Doppler sonography of synovitis: assessment of therapeutic response-preliminary observations. Radiology 1996;198:582–4